ANALISIS KEMAMPUAN DAN KEMAUAN MEMBAYAR PETUGAS PARKIR TERHADAP PELAYANAN PUSKESMAS DI KABUPATEN BANYUMAS - Arif Kurniawan; Arih Diyaning Intiasari (Kesmas Indonesia, 2012)
ABSTRACT Different levels of ability and willingness to pay society encourages research to see how much the level of ability and willingness of the community especially the informal sector workers who are vulnerable to disease. Parking attendants who have no fixed income, and working outdoors is an object of research is interesting to examine the ability to pay and willingness to pay for public health care in Banyumas district. This descriptive research used consumption survey by 1 month recall for food budget and non food budget to scalling ATP. The Contingent Valuation Methode (CVM) used to scalling the WTP. Number of samples in this research is 40 people. Parking attendants in Banyumas District have Average of ATP was Rp. 21.706,6. The respondents have average of WTP Rp. 9262,5 for outpatient service in public health centers. The respondents have average of WTP Rp. 121.500,0 for inpatient service in public health centers. The ATP of the parking attendant health services is higher than the WTP outpatient of the parking attendant, and is lower than the WTP inpatient of the parking attendant. Parking attedants should follow the health insurance so that if the events requiring inpatients service in public health centers. Keywords : Ability to Pay, Willingness to Pay, Public Health Centre Kesmasindo. Volume 5(2) Juli 2012, hlm. 86 - 94